Effect of digital finance on inclusive green growth through technological innovation - Li, Ying; Fang, Yuanping (Innovation and development, 2025)
Inclusive green growth is crucial for sustainable economic development. Through subjective and objective comprehensive evaluation methods, this study measures the level of inclusive green growth for 30 provinces in China from 2011 to 2019. On this basis, the study uses multiple empirical methods to analyze the effect of digital finance on inclusive green growth. The results reveal that digital finance significantly promotes inclusive green growth through the mechanism of technological innovation. In addition, the threshold regression model indicates that digital finance has a marginally increasing effect under single threshold constraints of its development level and coverage breadth. However, digital finance has a marginally decreasing effect under the single threshold constraint of traditional finance development level. Finally, a heterogeneity test indicates that digital finance significantly promotes inclusive green growth in regions with low per capita GDP, those with a high agricultural GDP percentage, and central and western regions.